Pengaruh Konsumen Dalam Keputusan Pembelian Produk Melalui Tiktokshop - Karina Ristiyana; Dedi Mulyadi (Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the effect of using the Tiktok application on consumer purchasing decisions for products at Tiktokshop. The method used in this research is a quantitative method. the type of research used is research research with the method of distributing questionnaires. the sample in this study was 100 respondents and data processing using SPSS. This research has met the validation and reliability requirements. The variables used in this study are purchasing decision variables and the independent variable, namely the Tiktokshop application. The results of the study concluded that the use of the Tiktokshop Application has a positive effect on product purchasing decisions through Tiktokshop.